Finite Element Analysis of Geotechnical Isolation System Finite-Element Analysis on the Geotechnical Seismic Isolation (GSI) System (British Journal of Multidisciplinary and Advanced Studies, 2023)
In order to verify the effectiveness of the Geotechnical Seismic Isolation (GSI), a series of finite element parameter studies were carried out. The finite element calculation model of the GSI system and superstructure is established. The finite element analysis conditions consist of two kinds of confining pressures, three kinds of RSM ratios and three kinds of seismic wave inputs, a total of 32 kinds of conditions. Comparing the analysis results of the parameters, it can be seen that the dynamic shear modulus of the RSM sample increases with the increase of the confining pressure, but the degree is affected by the input of seismic waves. The greater the peak value of the input acceleration, the more obvious the isolation effect; As the RSM ratio increases, it decreases, but it is not greatly affected by the input of seismic waves, and the isolation effect remains basically the same. The numerical simulation results verify the isolation effect of GSI, which can be used as a reference for practical engineering applications in the future.